The Impact of Alluvial Land Subsidence Towards Extension of Inundation and Infrastructure Damage At Settlements Around Harbor Area of Tanjung Mas – Semarang - Soedarsono . (International Conference on Coastal and Delta Areas, 2015)
Semarang is the capital of Central Java province of Indonesia, has an area of 373.4 km 2 with population of 1.571.341 million. Southern parts of this city are hilly, denudational and volcanic areas, whereas alluvial areas are located in the northern part of this place. In the alluvial areas, the land around keeps undergoing subsidence and this becomes a serious issue especially to the area growing naturally in the estuary area of Semarang River. While high tide is happening, sea water comes to thesettlements through some rivers and floods, as a result, settlement infrastructures are damaged and this potentially causes deseases. This research used survey method, evaluation towards the extention of inundation in the settlement over 941.14 Hectare, the resut would be a change on the extension of inundation in the settlement. Data analysis was conducted by using Geographic Information System (GIS). To know the impact of inundation to the settlement towards infrastructure damage, statistic with cross tabulation was used while deseases suffering by people around and health level due to the inundation, the analysis used the software of Statistical Product Service Solution (SPSS) version 16. Result of the research showed the year of 1996 (167,25 Hectare), year of 2010 (138,09 Hectare) andyear of 2015 (70,25 Hectare) from SPSS analysis in 2010. The result due to the inundation was happened settlement in the estuary in the amount of 20.10%. Between year of 2010 and 2015, was happened at the settlement to the inundation, caused by river normalization of Asin’s river and start functioning the pond’s retention Semarang river, settlement infrastructures are damaged and thispotentially causes deseases.